Activation of adenosine A2A but not A2B receptors is involved in uridine adenosine tetraphosphate-induced porcine coronary smooth muscle relaxation - Changyan Sun; Tong Jiao; Daphne Merkus; Dirk J. Duncker; S. Jamal Mustafa; Zhichao Zhou (Elsevier, 2019)
Activation of both adenosine A2A and A2B receptors (A2BR) contributes to coronary vasodilation. We previously demonstrated that uridine adenosine tetraphosphate (Up4A) is a novel vasodilator in the porcine coronary microcirculation, acting mainly on A2AR in smooth muscle cells (SMC). We further investigated whether activation of A2BR is involved in Up4A-mediated coronary SMC relaxation. Both A2AR and A2BR may stimulate H2O2 production leading to activation of KATP channels in SMCs, we also studied the involvement of H2O2 and KATP channels in Up4A-mediated effect. Coronary small arteries dissected from the apex of porcine hearts were mounted on wire myograph for Up4A concentration responses. Up4A-induced coronary SMC relaxation was attenuated by A2AR but not A2BR antagonism or non-selective P2R antagonism, despite greater endogenous A2BR expression vs. A2AR in both coronary small arteries and primary cultured coronary SMCs. Moreover, Up4A-induced coronary SMC relaxation was blunted by H2O2 catabolism. This effect was not altered by KATP channel blockade. Combination of H2O2 catabolism and A2AR antagonism attenuated Up4A-induced coronary SMC relaxation to the similar extent as A2AR antagonism alone. Collectively, Up4A-induced porcine coronary SMC relaxation is mediated by activation of A2AR-H2O2 pathway. This process does not involve A2BR, P2R or KATP channels. Keywords: Up4A, Coronary microcirculation, Relaxation, Smooth muscle cells, Adenosine